BUDAYA EGALITARIANISME PEREMPUAN MADURA DALAM TAREKAT NAQSYABANDIYAH - Achmad Mulyadi (Institut Agama Islam Negeri Madura, 2015)
This article elaborates women issues based on the text comprehension and cultural construction of follower of the Naqsyabandiyah order in Madura. From the description, it was found that women's awareness of the status and rights increased so that become more independent. Women des-perately need privileges and equal status with men, including in terms of achieving the highest spirituality. Cultural construction of this kind can be found in the Naqshbandi Muzhariyah follower in Madura. The existence of such women murshid such as Nyai Tobibah, Nyai Aisha, and Fathimah Syarifah in tarekat showed that the organizational culture is no obstacle for women to reach the highest spirituality.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i1.614